2022
DOI: 10.1002/cjoc.202100822
|View full text |Cite
|
Sign up to set email alerts
|

Sequential One‐Pot Three‐Enzyme Synthesis of the Tetrasaccharide Repeating Unit of Group B Streptococcus Serotype VIII Capsular Polysaccharide

Abstract: The biochemical property and functional identification of three recombinant glycosyltransferases, including β-1,4-rhamnosyltransferase (Cps8R), β-1,4-galactosyltransferase (Cps8J) and α-2,3-sialyltransferase (Cps8K) involved in the biosynthesis of the tetrasaccharide repeating unit of serotype VIII capsular polysaccharide (CPS) of Group B Streptococci (GBS), were systematically investigated. Subsequently, these recombinant enzymes were employed for one-pot three-enzyme efficient synthesis of the tetrasaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…As depicted in Figure 5 , the reaction velocity catalyzed by WciN was dramatically reduced as the concentration of Glcα-PP-(CH 2 ) 11 -OPh 1 was greater than 0.25 mM, indicating the activity of WciN could be easily inhibited even by a slightly higher concentration of acceptor substrate. This finding was radically different from those reported glycosyltransferases that could well accept Glcα-PP-(CH 2 ) 11 -OPh 1 as substrate acceptor ( Wang et al, 2019 ; Liang et al, 2022 ). Bioinformatics analysis of the amino acid sequence of WciN revealed that there was no transmembrane domain in WciN, lacking a domain that interacts with the membrane.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…As depicted in Figure 5 , the reaction velocity catalyzed by WciN was dramatically reduced as the concentration of Glcα-PP-(CH 2 ) 11 -OPh 1 was greater than 0.25 mM, indicating the activity of WciN could be easily inhibited even by a slightly higher concentration of acceptor substrate. This finding was radically different from those reported glycosyltransferases that could well accept Glcα-PP-(CH 2 ) 11 -OPh 1 as substrate acceptor ( Wang et al, 2019 ; Liang et al, 2022 ). Bioinformatics analysis of the amino acid sequence of WciN revealed that there was no transmembrane domain in WciN, lacking a domain that interacts with the membrane.…”
Section: Resultscontrasting
confidence: 99%
“…We have recently reported the optimized synthesis of the glycolipid Glcα-PP-(CH 2 ) 11 -OPh 1 ( Liang et al, 2022 ) and utilized it as an acceptor substrate to characterize several bacterial glycosyltransferases related to CPS RU biosynthesis ( Wang et al, 2019 ; Wang et al, 2021 ; Liang et al, 2022 ). Therefore, using it as an enzymatic substrate, the detailed biochemical properties of WciN were then investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations